A market-based mechanism for integration of mobile devices into mobile grids. (6th July 2010) - Chunlin, Li; Layuan, Li
In a mobile grid, energy resources distribution and computation workloads are not balanced within mobile devices. Some mobile devices have spare energy; some mobile devices are energy exhausted. In this paper, we present a market-based mechanism for efficient integration of mobile devices into mobile grids to optimise the system performance. All mobile devices in a mobile grid can be classified into different roles, such as buyers (consumers) and sellers (providers). Using market-based cooperation among devices, an energy saving scheme is proposed for a mobile grid. The paper is targeted to solve energy allocation of mobile devices by using the utility-based scheme. The system utility of a mobile grid is maximised when the equilibrium prices are obtained through the device market optimisation. A market-based algorithm for integration of mobile devices into a mobile grid is proposed. In order to test the performance of the algorithm, simulation is conducted by comparing with other power-aware scheduling in mobile grids.